Vehicular Ad Hoc Networks Security for Smart Cities Based on 2D ZCC/MD Optical CDMA Code - Matem, R. (Springer, 2020)
Due to the increasing numbers of vehicles in the world which results in a rise in traffic density, smart city is seeking to minimize transportation problems such as accidents. To solve this issue, VANET has been developed to improve vehiclesâ mobility and provide a safe city. VANET is a type of wireless technology which provides vehicle-to-vehicle (V2V) and vehicle-to-infrastructures (V2I) communication system. Despite the advantages of VANET, it faces a lot of challenges; security and privacy, for instance, are the most critical ones. In this paper, we implement an approach used in Optical CDMA system given its success in optical domain. This technique is based on the 2D ZCC/MD code which is characterized by zero cross-correlation property. The transmission system is based on the VLC system, in which the information will circulate in optic domain using light in free space. The proposed system can provide the security and the privacy due to the 2D ZCC/MD code which assigns each user by a specific unique code. Â© 2020, Springer Nature Singapore Pte Ltd.